Phytostabilisation of tailing ponds with use of water absorbing geocomposites and organic and mineral additives - Kuc, Piotr; Kordas, Leszek; Lejcuś, Krzysztof (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
The effectiveness of reclamation activities in a tailing pond has been evaluated by the application of mineral and organic substances and remediation plants with water absorbing geocomposites. The research was conducted on the tailing pond of the former copper mine in Iwiny, Poland, basing on a strict, trifactorial experiment set up with the use of the split-split-plot method with 4 replications. The main experimental factors were the variants of substrate modification, various species (or mixtures) of reclamation plants and the presence of water absorbing geocomposites. The conducted experiments did not demonstrate a significant influence of various types of tailing additives. The usability of individual species of reclamation grass or their mixtures for the reclamation was similar. Water absorbing geocomposites contributed to the improvement of difficult vegetation conditions that occur in tailing ponds.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 71-81
Keywords: ochrona środowiska; inżynieria środowiska